2013
DOI: 10.1128/jvi.01666-13
|View full text |Cite
|
Sign up to set email alerts
|

Standard Trivalent Influenza Virus Protein Vaccination Does Not Prime Antibody-Dependent Cellular Cytotoxicity in Macaques

Abstract: Yearly vaccination with the trivalent inactivated influenza vaccine (TIV) is recommended, since current vaccines induce little cross neutralization to divergent influenza strains. Whether the TIV can induce antibody-dependent cellular cytotoxicity (ADCC) responses that can cross-recognize divergent influenza virus strains is unknown. We immunized 6 influenza-naive pigtail macaques twice with the 2011-2012 season TIV and then challenged the macaques, along with 12 control macaques, serially with H1N1 and H3N2 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…We found that young adults with no known prior exposure to (consistent with a lack of HI Abs that recognized) a 1968 H3N2 virus had robust ADCC-mediating Abs to this strain (36). In our studies, most influenza virus-specific ADCC-mediating Abs induced via vaccination or infection were shown to be broadly reactive to strains within a given subtype (32,34,(44)(45)(46). However, we detected cross-reactive ADCC-mediating Abs toward avian H5N1 and H7N7 strains in some individuals in the absence of prior exposure (36).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…We found that young adults with no known prior exposure to (consistent with a lack of HI Abs that recognized) a 1968 H3N2 virus had robust ADCC-mediating Abs to this strain (36). In our studies, most influenza virus-specific ADCC-mediating Abs induced via vaccination or infection were shown to be broadly reactive to strains within a given subtype (32,34,(44)(45)(46). However, we detected cross-reactive ADCC-mediating Abs toward avian H5N1 and H7N7 strains in some individuals in the absence of prior exposure (36).…”
mentioning
confidence: 64%
“…Studies on HIV ADCC by our group showed that ADCC can be mediated to peptides derived from internal HIV proteins, including Pol and Vpu (72,73). Our limited studies in macaques suggest that anti-NP Abs mediate ADCC activity, because anti-NP Abs could activate macaque NK cells in vitro (46). Further studies are required to determine whether virus-infected cells expressing NP can be killed by ADCC, as well as the ability of anti-NP ADCCmediating Abs to mediate protection in vivo.…”
Section: Adcc-mediated Activity Toward Internal Proteins Of Influenzamentioning
confidence: 99%
“…The correlation between amount of virus produced and induction of functional antibody responses against the virus and mutual relationship between total antibody response and induction of functional antibodies may provide a basis for analyzing vaccine effectiveness in relation to natural infection in humans. For instance, Jegaskanda has already demonstrated that ADCC is associated with control of pandemic H1N1 influenza virus infection in macaques (37), but ADCC antibodies were not induced following standard trivalent influenza virus protein vaccination (25). These data may also be relevant in view of the discussion of appropriate correlates of protection, identifying which immune responses are responsible for viral clearance.…”
Section: Discussionmentioning
confidence: 96%
“…The dose-finding studies are commonly not performed in NHP, and only a few studies have addressed the induction of adaptive immune responses after viral challenge in macaques (24)(25)(26). No correlation was drawn between levels of virus production and strength or neutralizing capacity of the induced antibody responses.…”
mentioning
confidence: 99%
“…However, the extent to which TIV induces ADCC and other Fc-medi-ated Ab functions such as ADP has not been well studied. A seasonal TIV vaccine failed to elicit ADCC Abs in influenza-naive pigtail macaques (13); however, studies in animal models do not recapitulate the complex immune landscape from multiple prior influenza exposures in human adults. Since HIV can cause widespread B cell dysfunction (14), there is a need to understand nonNAb responses to influenza in subjects with HIV infection and how these are modulated by vaccination.…”
mentioning
confidence: 99%